The use of Powder Metallurgy for promoting friction reduction under sliding-rolling lubricated conditions. (May 2021) - Boidi, G.; Profito, F.J.; Kadiric, A.; Machado, I.F.; Dini, D.
Abstract: This work exploits the use of different sintering manufacturing techniques for obtaining superior performances in lubricated point contacts. Disc and ball specimens were manufactures varying porosity and pore characteristics. The effect of surface pores in sintered materials was evaluated based on the frictional behaviour under different sliding-rolling conditions and lubrication regimes. Furthermore, lubricant film thicknesses were measured using interferometric technique. Test results showed that the decrease of porosity generally improves tribological performance. Low porosity surfaces can promote friction reduction compared to non-porous reference materials in specific configurations and operating with similar specific lubricant thickness values. This work contributes to an improved understanding of how randomly distributed micro-irregularities could change lubrication conditions, potentially increasing the efficiency of lubricated mechanical systems. Highlights: Tribological performance of sintered samples in sliding-rolling tests. Manufacturing of both ball and disc sintered samples. Film thickness measurements of porous surfaces. The reduction of surface porosity and pores dimensions reduce friction. Small round pores improve tribological performances compared to non-porous surfaces.